2012
DOI: 10.1080/19361653.2012.628230
|View full text |Cite
|
Sign up to set email alerts
|

What's Good About Being Gay? Perspectives from Youth

Abstract: This article explores gay and bisexual male adolescents’ positive perceptions of their sexual orientation identity. In-depth qualitative interviews were conducted with an ethnically diverse sample of 63 gay/bisexual male adolescents in Chicago (N=42) and Miami (N=21). Data revealed two major conceptual categories: 1) positive personal conceptualizations of being gay/bisexual, and 2) resiliency in the face of gay-related oppression. Additional primary themes and sub-themes were identified within each category t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…14 In addition, gay and bisexual adolescents may evidence strength and resilience related to their shared sexual orientation culture and the supportive relationships that may exist for them in the larger gay community. [46][47][48][49] Heterosexual young women living with HIV often have different life experiences than gay/bisexual young men living with HIV, as several authors have suggested that women living with HIV experience various forms of stigmatization in their relationships with others. [50][51][52] Quantitative studies have STIGMA IN YOUTH NEWLY DIAGNOSED WITH HIV revealed that women living with HIV experience more social rejection, shame, discrimination, violence, and overall perceived HIV stigma than men with HIV/AIDS.…”
Section: Gender Differences In Stigma Reductionmentioning
confidence: 99%
“…14 In addition, gay and bisexual adolescents may evidence strength and resilience related to their shared sexual orientation culture and the supportive relationships that may exist for them in the larger gay community. [46][47][48][49] Heterosexual young women living with HIV often have different life experiences than gay/bisexual young men living with HIV, as several authors have suggested that women living with HIV experience various forms of stigmatization in their relationships with others. [50][51][52] Quantitative studies have STIGMA IN YOUTH NEWLY DIAGNOSED WITH HIV revealed that women living with HIV experience more social rejection, shame, discrimination, violence, and overall perceived HIV stigma than men with HIV/AIDS.…”
Section: Gender Differences In Stigma Reductionmentioning
confidence: 99%
“…Focus groups pose additional challenges to moving around (some researchers have attempted this), and are most often conducted stationary. Certainly, there are important qualitative studies recently conducted with LGBTQ youth that have explored social influences using stationary oral/written storytelling narrative techniques (Bond & Loewenstern, 2014; Harper, Brodsky, & Bruce, 2012; Hillier, Mitchell, & Ybarra, 2012; Olive, 2012; Trocki, Michalak, & Drabble, 2013). Go-along interview methods present opportunities to overcome the constraints of stationary qualitative techniques and expand the utility of open-ended interviewing, as well as increases youth ownership and direction over the data collection experience.…”
Section: Introductionmentioning
confidence: 99%
“…As Harper, Jernewall and Zea (2004) argue, the voices of healthy Black sexual minorities are almost entirely absent in the academic literature. In particular, much of the literature addressing the HIV burden among Black GBM focuses on poor outcomes and the conditions giving rise to negative health (Harper, Brodsky & Bruce, 2012). Many Black GBM thrive despite marginalization, suggesting a need for a concomitant line of research focused on resilient Black GBM.…”
Section: Introductionmentioning
confidence: 99%